Double-Needle Arthrocentesis with Viscosupplementation in Patients with Temporomandibular Joint Disc Displacement without Reduction (Clinics, 2021)
OBJECTIVES: Arthrocentesis is the simplest surgical intervention for the temporomandibular joint (TMJ). It can be performed on an outpatient basis at a low cost and with low morbidity. The objective is to release the articular disc by disrupting the adhesion formed between its surfaces and the mandibular fossa through hydraulic pressure generated by irrigation of the upper compartment of the TMJ. Viscosupplementation with hyaluronic acid during or after arthrocentesis improves clinical outcomes, increases mouth opening, and reduces pain levels. The aim of this study was to evaluate the efficiency of arthrocentesis plus hyaluronic acid viscosupplementation through clinical examination and preoperative magnetic resonance imaging in patients with unilateral disc displacement without reduction (DDwoR). METHODS: This analytical retrospective cross-sectional study clinically and radiologically evaluated 72 patients of both sexes with unilateral DDwoR. The following data were collected: sex, pain, age, duration of pain, maximum mouth opening, and patient pain perception on a visual analog scale. TMJ arthrocentesis was performed only once for each of the indicated joints. Data were collected before arthrocentesis (baseline) and at 7, 14, 30, 60, 90, and 180 days after the procedure (final evaluation). RESULTS: Between the baseline and final evaluation, there was a significant reduction in pain (p=0.001) and restoration of articular function. In addition, there was a significant increase in maximum mouth opening (p=0.001). CONCLUSION: Patients with DDwoR undergoing arthrocentesis combined with hyaluronic acid injection showed significant improvement in the perceived pain and maximum mouth opening in the mid-term follow-up periods.